A phenomenological study on the meaning of educational justice for street children. (March 2019) - Nouri, Ali; Karimi, Yousef
A phenomenological study was conducted to obtain an understanding of the meaning of educational justice for street-working children in Tehran, Iran. The data were obtained through observation and semi-structured interview from 22 children aged between 5 and 15 years old (13 male and 9 female) who were selected based on their cooperation through a convenience sampling technique. The children's responses to the interview questions regarding their perceptions of educational justice and the other related concerns were coded and a set of categories were developed. The results of the study indicated that poverty and parental negligence are the two primary and interrelated reasons that lead children to work on streets and consequently limit their access to formal education. The participants viewed educational justice as providing all children with adequate opportunities for access to formal education and establishing effective mechanisms for a fair distribution of resources and facilities in a way that all disadvantaged children including street children could benefit from and engage in productive activities of the society. They expected that educational system should not only be responsible for providing education for all but also to show greater concern and effort for the children with special needs. The present condition of street children necessitates better future policy-making to develop practical solutions in order to meet the basic educational needs of street children more efficiently and equitably.